DEVELOPMENT AND IMPLEMENTATION OF SYSTEMS OF THE TECHNOLOGICAL ACCOUNTING AND CONTROL USING WEBTECHNOLOGIES . . . . . . . . . . . . . . . . - A. O. Burenkov (Литьë и металлургия)
This article has review and methodical character. It will be useful for employees of automation service of the state and private enterprises.